Description of female genitalia, additional morphological variations, and courtship behavior and copulation of Macrostemum brasiliense (Fischer 1970) (Trichoptera: Hydropsychidae) - Silva, Larissa Moreira; Paprocki, Henrique (Zootaxa, 2020)
Macrostemum Kolenati 1859 is a cosmopolitan caddisfly genus with 105 described species easily recognized by the remarkable contrasting dark and clear wing patterns. The larvae of the genus build retreats with capture nets adapted to filter fine particulate organic matter. The genus has 19 described, Neotropical species, almost all described only by wing patterns and male genitalia. To date, only two Neotropical species have an associated immature stage and only one has the female genitalia described. Macrostemum brasiliense occurs in southeastern Brazil, primarily in the Atlantic Rainforest. The species has characteristic wing and body patterns, and phallic morphology recorded in literature and further described here. We contribute to knowledge of this species by further describing and illustrating the female genitalia, adding detail about wing variation patterns and venation, including the intriguing melanic female variation. This conspicuous Atlantic Rainforest caddisfly is now among the best-known species of Neotropical Trichoptera.